Problem-Based Learning to Improve Problem-Solving Skill: Is it Effective Enough? - Asyhari, Ardian; Sifa’i, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to determine the effectiveness of the problem based learning model on the problem solving ability of high school students. This research is a quasy experimental research with the matching only pretest-posttest control group design. The subjects in this study were students of class XI IPA SMA Negeri 1 Ulubelu. The effect size hypothesis test is used to obtain the results of the effectiveness of the PBL model on students’ problem solving abilities. The result of the effect size hypothesis test showed the value of 0.68 in the moderate category. So it can be concluded that the problem-based learning model is effective for improving the problem-solving ability of high school students.